add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
1a+3b 2a+4b=3a +7b
3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2
a + 7b + 2c
The given expression can be simplified to: 3b-a
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
9a + 7b *remember to look and understand the letters!*
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
Numerically, if the question looks like this:--(3a + 7b) - 8a - 4b + 2Then the answer is this:--3a - 7b - 8a - 4b + 2= -11a -11b + 2
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
10a+7b undefined variables cannot be determined
7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4
If: 6b+21 = 7b-21 Then: 6b-7b = -21-21 And: -b = -42 So: b = 42
-7 7b + 15 = (-34) 7b = (-34) - 15 7b =(-49) b = (-49) / 7 b= (-7)
It is an equation and the value of b is 3
Sometimes you can think of things instead of letters, for example...3a + 2a = ?If that was 3 apples plus 2 apples equals ... ? then you could do it, right?3 apples + 2 apples = 5 apples3a + 2a = 5aAnd the same with MINUS...10b - 7b = ?10 bananas - 7 bananas = 3 bananas10b - 7b = 3bOf course, you can't add bananas and apples, you have to count them separately, so...3a + 4b + 7a - 2b= 3 apples + 4 bananas + 7 apples - 2 banana= 10 apples + 2 bananas= 10a +2b(You can't add these two together)After that it gets more complicated...
It is: 19b+7b = 26b
3b -2 =7 b+4
It is: 7b+10 simplified